Peningkatan Aktivitas dan Hasil Belajar Biologi melalui Group Investigation - Suryani, Faizah (Universitas Muhammadiyah Magelang, 2020)
Abstract Student biology learning outcomes are still low (under the KKM) caused by several things, both those originating from students, teachers and facilities and infrastructure that are underutilized. The purpose of this class action research is to increase the learning activities and learning outcomes of students after participating in the biology learning process with a GI (Group Investigation) type of cooperative learning model. The research method used was Classroom Action Research which was conducted in two cycles. Each cycle consists of three meetings and four stages, namely planning, action, observation, and reflection. The subjects of this study were 30 students of Class XI MIPA-2, consisting of 7 men and 23 women. The research instrument used was a test of learning outcomes in the form of objective tests in the form of multiple choice and essays or descriptions. The results showed that the application of the GI (Group Investigation) type of cooperative learning model could increase students' learning activities and outcomes. The results of the first cycle of activity amounted to 76.67 percent, classical learning completeness 80 percent with an average of 74.61. And in the second cycle of activity by 90 percent, classical learning completeness 93.33 percent with an average of 80.83 Thus the second cycle has met the target achievement indicator (IPH), because it has reached more than 85 percent. There is a correlation (relationship) with the high category between activity and learning outcomes, which is 0.820 in cycle I and 0.854 in cycle 2.